Anesthetic Considerations for Patients on Psychotropic Drug Therapies - Monica W. Harbell; Catalina Dumitrascu; Layne Bettini; Soojie Yu; Cameron M. Thiele; Veerandra Koyyalamudi (Neurology International, 2021)
Psychotropic drugs are used in the treatment of psychiatric and non-psychiatric conditions. Many patients who are on psychotropic medications may present for procedures requiring anesthesia. Psychotropic medications can have dangerous interactions with drugs commonly used in anesthesia, some of which can be life-threatening. In this review, we describe the current anesthetic considerations for patients on psychotropic drug therapies, including antidepressants, antipsychotics, mood stabilizers, anxiolytics, and stimulants. The pharmacology, side effects, and potential drug interactions of the commonly prescribed psychotropic drug therapies with anesthetic agents are described. Further, we highlight the current recommendations regarding the cessation and continuation of these medications during the perioperative period.